Tempered Radon Measures - Kabanava, Maryia (Revista Matemática Complutense, 2008)
A tempered Radon measure is a σ-finite Radon measure in Rn which generates a tempered distribution. We prove the following assertions. A Radon measure μ is tempered if, and only if, there is a real number βsuch that ……. finite. A Radon measure is finite if, and only if, it belongs to the positive cone…….. (equivalent norms).